Corporate Restructuring From Cause Analysis to Execution - Vance, David; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Corporate Restructuring is a practical approach to rescuing troubled companies and driving underperforming companies to top performance. It combines proven restructuring strategies with rigorous theoretical analysis. This book explains how to set and achieve asset, staffing, sales and profit goals. Topics include diagnostic tools to identify the root cause of problems, the human dynamics that cause a company to thrive or wither, customer service and relationship marketing, customer intelligence systems, new product development, process mapping, continuous process improvement and re-engineering as well as integrating IT into corporate strategy. It is also discussed how to find the resources needed to keep a company alive during restructuring and how to use bankruptcy offensively and defensively. Corporate Restructuring emphasizes execution. All the restructuring theories in the world weigh less than a simple plan, well executed.
Diagnosing the Problem -- Setting Restructuring Goals and Reverse Engineering a Company -- People -- Labor Cost -- Evaluation of Businesses, Divisions, Facilities, and Dealerships -- Evaluation Products, Customers and Contracts -- Revenue Growth and New Products -- Markets and Pricing -- Customer Service and Relationships -- Re-engineering, Process Mapping, Continuous Process Improvement and Outsourcing -- Cost Analysis and Finding Waste -- Information Technology -- Financing the Turnaround -- Internal Sources of Cash -- Emergency Cash Management -- Bankruptcy -- Execution.
Keywords: Economics; Industrial management; Business planning; Economics/Management Science; Management/Business for Professionals; Organization/Planning.